Early increased density of cyclooxygenase-2 (COX-2) immunoreactive neurons in Down syndrome - Mulet, Maria; Blasco-Ibáńez, José Miguel; Crespo, Carlos; Nácher, Juan; Varea, Emilio (Folia Neuropathologica, 2017)
Neuroinflammation is one of the hallmarks of Alzheimer’s disease. One of the enzymes involved in neuroinflammation, even in early stages of the disease, is COX-2, an inducible cyclooxygenase responsible for the generation of eicosanoids and for the generation of free radicals. Individuals with Down syndrome develop Alzheimer’s disease early in life. Previous studies pointed to the possible overexpression of COX-2 and correlated it to brain regions affected by the disease. We analysed the COX-2 expression levels in individuals with Down syndrome and in young, adult and old mice of the Ts65Dn mouse model for Down syndrome. We have observed an overexpression of COX-2 in both, Down syndrome individuals and mice. Importantly, mice already presented an overexpression of COX-2 at postnatal day 30, before neurodegeneration begins; which suggests that neuroinflammation may underlie the posterior neurodegeneration observed in individuals with Down syndrome and in Ts65Dn mice and could be a factor for the premature appearance of Alzheimer’s disease.